Translation Loss and Gain in the Translation of Nias Cultural Jewelry Terms into English : Penelitian - Afore Tahir Harefa; Theresia Trines Anjelin Zai; Elnardus Fransiskus Jafrinus Namo; Yofita Gulo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aimed to investigate translation loss and gain in the translation of Nias cultural jewelry terms into Indonesian and English. A qualitative research design was employed, using museum books and catalogues from Museum Pusaka Nias as data sources. Data were analyzed through descriptive and comparative qualitative methods to identify instances of loss and gain in both target languages. The results revealed nine instances of gain, mostly involving the addition of descriptive words such as